At thermoneutrality, acute thyroxine-induced thermogenesis and pyrexia are independent of UCP1 - Dittner, Claudia (Molecular metabolism, 2019)
Objective: Hyperthyroidism is associated with increased metabolism (“thyroid thermogenesis”) and elevated body temperature, often referred toas hyperthermia. Uncoupling protein-1 (UCP1) is the protein responsible for nonshivering thermogenesis in brown adipose tissue. We hereexamine whether UCP1 is essential for thyroid thermogenesis.Methods:We investigated the significance of UCP1 for thyroid thermogenesis by using UCP1-ablated (UCP1 KO) mice. To avoid confoundingfactors from cold-induced thermogenesis and to approach human conditions, the experiments were conducted at thermoneutrality, and to resemble conditions of endogenous release, thyroid hormone (thyroxine, T4) was injected peripherally. Results: Both short-term and chronic thyroxine treatment led to a marked increase in metabolism that was largely UCP1-independent. Chronic thyroxine treatment led to a 1–2 °C increase in body temperature. This increase was also UCP1-independent and was maintained even at lower ambient temperatures. Thus, it was pyrexia, i.e. a defended increase in body temperature, not hyperthermia. In wildtype mice, chronic thyroxine treatment induced a large relative increase in the total amounts of UCP1 in the brown adipose tissue (practically no UCP1 in brite/beige adipose tissue), corresponding to an enhanced thermogenic response to norepinephrine injection. The increased UCP1 amount had minimal effects on thyroxine-induced thermogenesis and pyrexia. Conclusions These results establish that thyroid thermogenesis is a UCP1-independent process. The fact that the increased metabolism coincides with elevated body temperature and thus with accelerated kinetics accentuates the unsolved issue of the molecular background for thyroid thermogenesis.